Relation of serum copper status to survival in COVID-19 - Hackler, Julian; Heller, Raban; Sun, Qian; Schwarzer, Marco; Diegmann, Joachim; Bachmann, Manuel; Moghaddam-Alvandi, Arash; Schomburg, Lutz (Nutrients, 2021)
The trace element copper (Cu) is part of our nutrition and essentially needed for several cuproenzymes that control redox status and support the immune system. In blood, the ferroxidase ceruloplasmin (CP) accounts for the majority of circulating Cu and serves as transport protein. Both Cu and CP behave as positive, whereas serum selenium (Se) and its transporter selenoprotein P (SELENOP) behave as negative acute phase reactants. In view that coronavirus disease (COVID-19) causes systemic inflammation, we hypothesized that biomarkers of Cu and Se status are regulated inversely, in relation to disease severity and mortality risk. Serum samples from COVID-19 patients were analysed for Cu by total reflection X-ray fluorescence and CP was quantified by a validated sandwich ELISA. The two Cu biomarkers correlated positively in serum from patients with COVID-19 (R = 0.42, p < 0.001). Surviving patients showed higher mean serum Cu and CP concentrations in comparison to non-survivors ([mean+/−SEM], Cu; 1475.9+/−22.7 vs. 1317.9+/−43.9 µg/L; p < 0.001, CP; 547.2.5+/−19.5 vs. 438.8+/−32.9 mg/L, p = 0.086). In contrast to expectations, total serum Cu and Se concentrations displayed a positive linear correlation in the patient samples analysed (R = 0.23, p = 0.003). Serum CP and SELENOP levels were not interrelated. Applying receiver operating characteristics (ROC) curve analysis, the combination of Cu and SELENOP with age outperformed other combinations of parameters for predicting risk of death, yielding an AUC of 95.0%. We conclude that the alterations in serum biomarkers of Cu and Se status in COVID-19 are not compatible with a simple acute phase response, and that serum Cu and SELENOP levels contribute to a good prediction of survival. Adjuvant supplementation in patients with diagnostically proven deficits in Cu or Se may positively influence disease course, as both increase in survivors and are of crucial importance for the immune response and antioxidative defence systems.
Gesehen am 13.08.2021